2021
DOI: 10.1016/j.ekir.2021.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-analysis of Herpes Zoster Vaccine in Patients With CKD

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 56 publications
(139 reference statements)
1
2
2
Order By: Relevance
“…A significantly reduced risk of stroke (relative incidence = 0.58; 95% CI: 0.44–0.78) following the zoster vaccine live immunisation has been reported in a recent self-controlled case series study 16 . The main difference between our findings and numerous antecedent studies is that measure of association for the pre-specified adverse events was closer to one, or the confidence interval of the measure crossed one 5 , 6 , 8 , 13 , 16 , 22 . The apparent protective effect observed in our study could be attributed to the zoster vaccine’s live effectiveness against herpes zoster and associated complications, the healthy vaccine effect, delayed serious adverse events following vaccination, and healthy vaccine bias and healthy vaccinee time 14 , 16 .…”
Section: Discussioncontrasting
confidence: 91%
“…A significantly reduced risk of stroke (relative incidence = 0.58; 95% CI: 0.44–0.78) following the zoster vaccine live immunisation has been reported in a recent self-controlled case series study 16 . The main difference between our findings and numerous antecedent studies is that measure of association for the pre-specified adverse events was closer to one, or the confidence interval of the measure crossed one 5 , 6 , 8 , 13 , 16 , 22 . The apparent protective effect observed in our study could be attributed to the zoster vaccine’s live effectiveness against herpes zoster and associated complications, the healthy vaccine effect, delayed serious adverse events following vaccination, and healthy vaccine bias and healthy vaccinee time 14 , 16 .…”
Section: Discussioncontrasting
confidence: 91%
“…A 2021 meta-analysis by Hamed and colleagues, involving eight studies and 404,561 adults, found that the zoster vaccine live significantly reduced the risk of herpes zoster in patients with chronic kidney diseases (hazard ratio = 0.55, 95% CI 0.37-0.82). The heterogeneity (I² = 88%, p<0.01) was higher than that reported in our study (I² = 0%, p=0.93) (Hamad et al, 2021).…”
Section: Prisma Flow Diagramcontrasting
confidence: 85%
“…A significantly reduced risk of stroke (relative incidence = 0.58; 95% CI: 0.44-0.78) following the zoster vaccine live immunisation has been reported in a recent self-controlled case series study (Totterdell et al, 2020). The main difference between our findings and numerous antecedent studies is that measure of association for the pre-specified adverse events was closer to one, or the confidence interval of the measure crossed one (Gagliardi et al, 2019;Hamad et al, 2021;Totterdell et al, 2020;Tseng et al, 2012b). The apparent protective effect observed in our study could be attributed to the zoster vaccine's live effectiveness against herpes zoster and associated complications, the healthy vaccine effect, delayed serious adverse events following vaccination, and healthy vaccine bias and healthy vaccinee time (Baxter et al, 2012;Totterdell et al, 2020).…”
Section: Discussionsupporting
confidence: 42%
“…A total of 32 systematic reviews focused on non-COVID-19 vaccines ( Table 3 ). Several vaccines were studied, including inactivated hepatitis A vaccine [ 32 ], recombinant hepatitis B vaccine [ 33 , 34 , 35 , 36 , 37 , 38 ], recombinant human papillomavirus vaccines [ 39 , 40 ], inactivated influenza vaccine [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ], live-attenuated measles vaccine (given post hematopoietic stem-cell transplantation [ 52 ] and in children living with human immunodeficiency virus [ 53 ]), pneumococcal conjugate and polysaccharide vaccines [ 46 , 49 , 54 , 55 , 56 ], live-attenuated and recombinant subunit zoster vaccines [ 57 , 58 ], live-attenuated yellow fever vaccine [ 59 ], and others [ 60 , 61 , 62 , 63 ]. Immunocompromised states studied included use of B-cell-depleting anti-CD20 therapy, chronic kidney failure, human immunodeficiency virus infection, immune-mediated inflammatory diseases, liver cirrhosis, malignancy, post-splenectomy status, and solid organ transplant recipients.…”
Section: Resultsmentioning
confidence: 99%